Notes about Some Manuscripts Devoted to the Sufi Order of Yassawiyya - Hasan, Nadirhan (Journal of History Culture and Art Research, 2017)
No extensive and comprehensive study based on sources about Ahmad Yassawi and representatives of the Sufi order of Yassawiyya has been carried out since Ord. Prof. F.Koprulu’s well-known work “Turk Edebiyatinda Ilk Mutasavviflar” (First Sufi saints in Turkish literature). The discovery of new sources on the Yassawiyya offers new possibilities for research into this area and for introducing it to the world of science. This paper will present some general information on these newly discovered sources. The sources that are presented in this article are written by the followers of Khodja Ahmad Yassawi. These books tell about the life, thinking, the activities of Khodja Ahmad Yassawi, the opinions of his followers, the principles of the Sufi order of Yassawiyya, as well as the life and words of representatives of the Sufi orders like Naqshbandiyya, Kubraviyya and Ishqiyya, which were common in Central Asia. These books are very important sources in the field of research Yassawi, as they contains original information and documents about Yassawi and Yassawiyya.